K63-Linked Ubiquitination in Kinase Activation and Cancer - Wang, Guocan; Gao, Yuan; Li, Liren; Jin, Guoxiang; Cai, zhen; Chao, Jui-I; Lin, Hui-Kuan (Frontiers in Oncology, 2012)
Ubiquitination has been demonstrated to play a pivotal role in multiple biological functions, which include cell growth, proliferation, apoptosis, DNA damage response, innate immune response, and neuronal degeneration. Although the role of ubiquitination in targeting proteins for proteasome-dependent degradation have been extensively studied and well-characterized, the critical nonproteaolytic functions of ubiquitination, such as protein trafficking and kinase activation, involved in cell survival and cancer development, just start to emerge, In this review, we will summarize recent progresses in elucidating the nonproteolytic function of ubiquitination signaling in protein kinase activation and its implications in human cancers. The advancement in the understanding of the novel functions of ubiquitination in signal transduction pathways downstream of growth factor receptors may provide novel paradigms for the treatment of human cancers.